Mortality rate, conditions of vital activity among teenagers and youth in Siberia during 1990-2000 years - Ya. A. Leshchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The article presents the materials on the characterization of the indices of mortality among 15-19 years old. teenagers and. youth, in Siberia as well as the most important factors that influenced the change of these indices during 1991-2009 (on the example of the Irkutsk region). It was showed that main determinants of increase of the mortality rate of studied, group of people were social-economic shifts in the country among which the changes in the social-cultural environment had. the leading role. The aim. of the research was to study of peculiarities of changes of mortality of 15-19 years old. teenagers and. young people in conditions of Siberia during 1991-2009 years and. to reveal main determinants of these changes (on the example of Irkutsk region). Index of total mortality of boys during the researched period was 60 % higher than average indice in Russia, the one of girls was 37,8 % higher. As the result of the analysis of factors of environment, conditions of life and. indices of public health we determined that unfavorable dynamics of morbidity and. mortality was connected with social-economic transformations in the country and. with life level decrease in particular. In our opinion effect of social-economic transformations on the formation of early mortality of people was mediated by the condition of psychosocial ill-being of the society that included two components - psycosocial stress and. psycological health disorders. In this social-demographic situation it's necessary for educational and. public health institutions to elaborate and. introduce effective system of medicoprophylactic measures in the institutions of general education. This system's main component is developement of motivation, skills and. necessity of healthy life style in schoolchildren, formation of negative attitude to the smoking, alcohol, abused drugs and. prevention of formation of suicidal behaviour.